Type 4 Congenital Pouch Colon without Fistula with Anal Agenesis and Lower Vaginal Agenesis in a Female Fetus: A Rare Autopsy Case Report - Smita Singh; Shabnam Karangadan; Reema Bhushan; Kiran Agarwal (Turkish Journal of Colorectal Disease, 2019)

(untitled)
Congenital pouch colon is a rare anorectal malformation of unknown embryogenesis in which all or part of the large intestine is replaced by a pouch-like dilatation that usually communicates with the urogenital tract via a fistula. This condition is more common among males in North Indian population and is associated with various anomalies such as uterovaginal malformations. It has been classified into five types that are showing a shift over the years towards less severe types such as type 4. We report a case of type 4 congenital pouch colon with anal agenesis without fistula and lower vaginal agenesis in a 29-week-old female fetus diagnosed during autopsy. The absence of a fistula and association with vaginal agenesis in a female fetus, which gets overlooked even in live births, makes it a unique case. Early prenatal diagnosis and awareness about this condition are essential for appropriate management and favorable surgical outcome.